AN ENZYMOCYTOCHEMICAL STUDY OF ALKALINE PHOSPHATASE ISOENZYMES IN GASTRIC CANCER -- LIGHT AND ELECTRON MICROSCOPIC OBSERVATIONS - Su, Yinghao; Yang, Guanghn; Dong, Yuming; Zhang, Hong; Wu, Jifeng; Wang, Daobin (Chinese Journal of Cancer Research, 2013)
By using light and electron microscopic cytochemical technique, the activities and distributions of AP isoenzymes in gastric cancers and benign gastric diseases were examined. The results showed: Nagao, Regan and Kasahara isoenzym~, which were not expressed in normal gastric mucosae and non- malignant lesions, might be considered as tmnor markers of gastric conccr; The epithelimn of intestinal metaplasia exhibited intestinal- type AP only, which was one of the markers of well - differentiated intestinal metaplusia. In the view - point of the gene expression of AP isoenzymes, two mutation hypothesis and recessive - gene mutation hypothesis might be fit for gastric cancer.